Self-Appraisal among Engineering Undergraduates in Delivering Technical Oral Presentation in a Public University of Malaysia - Benraghda, Abdelmadjid; Noor Raha, Mohd Radzuan (IJEE, 2017)
Alternative assessment has increasingly gained attention in L2 speaking. One of the research areas which have received much significant attention in the literature of EFL/ESL is the use of self-appraisal technique. The aim of the current study is to find the engineering undergraduates’ conceptions about the use of self-appraisal on the technical oral presentation. For this purpose, 30 engineering ESL undergraduates were involved in this study from the Faculty of Civil Engineering & Earth Resources. They were then randomly chosen in order to delve into their perceptions pertaining to self-appraisal. A questionnaire was adapted from different studies. The results of the study showed that the questionnaire was reliable. The reliability coefficient of the conceptual study that was obtained indicated that the instrument was satisfactory and reliable for the study goals. Furthermore, the engineering undergraduates’ perceptions pertaining to self-appraisal was positive. Based on the obtained results, it was concluded that using self- appraisal strategy among Malaysian engineering undergraduates could be helpful in overcoming some of their oral presentation hindrances when they are assigned to deliver their technical oral presentations. Hence, the findings of this study have clear